Analysis of the Regional Regulation (PERDA) of Bantul Regency Number 6 of 2022 Regarding the Implementation of Village-Owned Enterprises - Rifa’i Setya Aji Pradana; Vicki Dwi Purnomo; Benedictus Hestu Cipto Handoyo; Syukron Abdul Kadir (PT FORMOSA CENDEKIA GLOBAL, 2023)
Village Owned Enterprises or Joint Village Owned Business Entities are economic institutions whose approach is expected to be able to move the wheels of the economy in the village. By implementing various kinds of procedures and the composition of structural officials and their duties and responsibilities that have been regulated in regional regulations, it is hoped that they can explore the potentials that exist in each sub-district so that they can improve people's welfare. If a village or business entity owned by a joint village administration is carried out, the settlement or dismissal will be carried out with the procedures stipulated in the regional regulation, with all decisions regarding planning, management, and evaluation remaining under the umbrella of joint deliberations.